(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
This research is aimed at study of braking efficiency of bus that is equipped with an anti-blocking pneumatic braking system. The braking efficiency test results, obtained in this research, are different from those used by car expert specialists in a car accident investigation. Therefore, practical recommendations on usage of those test results in the expert practice are given. Keyword:bus, brake tests, slow, expertise, traffic accident.